Yak (Bos grunniens) milk improves bone mass and microarchitecture in mice with osteoporosis - Xiaotong Li; Jin Zhang; Xianglin Kong; Talaygul Xerenbek; Torkun Mamet (Journal of Dairy Science, 2022)
ABSTRACT: The effect of milk on bone health is controversial. In this study, the effects of yak milk in mice with retinoic acid-induced osteoporosis (OP) were evaluated. Yak milk was provided to OP mice as a nutrition supplement for 6 wk. The results showed that yak milk significantly reduced bone turnover markers (tartrate acid phosphatase and alkaline phosphatase). The yak milk treatment was also associated with remarkably increased bone mineral density, bone volume, trabecular thickness, and trabecular number, as well as improved biomechanical properties (maximum load and stress) of the tibia. Furthermore, yak milk mitigated the deterioration of the network and thickness of trabecular bone in treated OP mice compared with the OP model group. The results indicated that yak milk could improve bone mass and microarchitecture through the inhibition of bone resorption in OP mice.